Dietary magnesium and DNA repair capacity as risk factors for lung cancer - Mahabir, Somdat (Oxford University Press, 2008)
Magnesium (Mg) is required for maintenance of genomic stability; however, data on the relationship between dietary Mg intake and lung cancer are lacking. In an ongoing lung cancer case–control study, we identified 1139 cases and 1210 matched healthy controls with data on both diet and DNA repair capacity (DRC). Dietary intake was assessed using a modified Block-NCI food frequency questionnaire and DRC was measured using the host-cell reactivation assay to assess repair in lymphocyte cultures. After adjustment for potential confounding factors including DRC, the odds ratios (ORs) and 95% confidence intervals (CIs) for lung cancer with increasing quartiles of dietary Mg intake were 1.0, 0.83 (0.66–1.05), 0.64 (0.50–0.83) and 0.47 (0.36–0.61), respectively, for all subjects (P-trend < 0.0001). Similar results were observed by histology and clinical stage of lung cancer. Low dietary Mg intake was associated with poorer DRC and increased risk of lung cancer. In joint effects analyses, compared with those with high dietary Mg intake and proficient DRC, the OR (95% CI) for lung cancer in the presence of both low dietary Mg and suboptimal DRC was 2.36 (1.83–3.04). Similar results were observed for men and women. The effects were more pronounced among older subjects (>60 years), current or heavier smokers, drinkers, those with a family history of cancer in first-degree relatives, small cell lung cancer and late-stage disease. These intriguing results need to be confirmed in prospective studies.